Performance of Biocemented Sydney Sand using ex-situ mixing technique - Youventharan, Duraisamy; Airey, David (Maney, 2015)
This paper describes a small-scale demonstration of an ex situ mixing technique that uses biocementation as an alternative to existing ground improvement techniques. The main objective of this research is to improve the strength and the stiffness of loose sand. Biocemented sand specimens have been produced by mixing a urease producing bacteria with nutrients and Sydney sand. Triaxial test with bender elements and the physical model test are conducted to investigate calcium carbonate precipitation and the properties of the soil. The model foundation tests have been performed at 1 g in a cylindrical tank with diameter of 600 mm. The tank has been filled with loose Sydney sand and a cemented column of 38 mm in diameter has been created in the center of the tank. A footing of 90 mm diameter has been placed on the sand surface and loaded to large displacements. The ability of the biocemented column made by ex situ mixing to significantly improve the foundation response is well demonstrated. Triaxial test performed on biocemented specimens also showed significant strength and stiffness increase over uncemented specimens. These tests confirmed the feasibility of using ex situ mixing technique to induce biocementation and provide valuable insight into the factors that must be considered in developing field applications.